(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied and calculated the diamagnetic coefficient for the neutral excitons confined in wobbled semiconductor self assembled quantum rings. We have systematically studied the impact of the rings reflection asymmetry on the excitons ground-state wave function localization, energy and diamagnetic coefficient. Using mapping method, we have reproduced three dimensional geometrical shapes and material compositions of the rings and simulated excitonic properties of the rings with the reflection symmetry and when the symmetry was broken. We have demonstrated that for the rings with reflection symmetry with respect to reflection in (110) plane Y-Z, the ground state excitons wave function is equally distributed between two potential valley of the rings. A small imbalance in geometrical or material characteristics of rings along the (110) direction of x-axis leaded to the localization of the potential valleys of the ring, which caused a significant decrease of the excitons diamagnetic coefficient. We have found that for the noninteracting particles, the electron wave function is more stable to the unbalance in the ring reflection symmetry than the hole wave function. This originates from the difference in the particles effective masses. The effective lateral radii of the electron and hole are shrinking rapidly when absolute values of the parameters are growing. This resulted in the rapid decrease of the neutral excitons diamagnetic coefficient. We have also found that a correlation imbalance in the ring geometry and material content has a recognizable impact on the ground state energy of the neutral excitons. The obtained results were found in good agreement with previously obtained results.